PENGARUH KUALITAS PRODUK DAN PENERAPAN NILAI ISLAM TERHADAP KEPUASAN NASABAH DI PT BANK MUAMALAT KANTOR CABANG MEDAN BALAIKOTA - Mhd. Rizky Al Akbar; Sugianto Sugianto; Aqwa Naser Daulay (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to analyze the effect of Product Quality and Application of Islamic Values on Customer Satisfaction. The research method used is quantitative methods. This study uses Non Probability Sampling. The sample in this study amounted to 87 respondents. The data collection instrument used a questionnaire. The dependent variable is the Customer Satisfaction variable and the independent variable is Product Quality and the Application of Islamic Values at Bank Muamalat Medan Branch Office. The data analysis method used is multiple regression. The results of this study indicate that (1) product quality has a partially significant effect on customer satisfaction; (2) the application of Islamic values partially significant effect on customer satisfaction; (3) product quality and application of Islamic values simultaneously have a significant effect on customer satisfaction at Bank Muamalat Medan Branch.